Do published guidelines for evaluation of Irritable Bowel Syndrome reflect practice? - Yawn, Barbara P (BioMed Central, 2001)
BACKGROUND: The only US guidelines listed in the National Guideline Warehouse for the diagnosis of Irritable Bowel Syndrome (IBS) are the expert opinion guidelines published by The American Gastroenterology Association. Although the listed target audience of these guidelines includes family physicians and general internists, the care recommended in the guidelines has not been compared to actual primary care practice. This study was designed to compare expert opinion guidelines with the actual primary care provided and to assess outcomes in the 3 years following the IBS diagnosis. METHODS: This is a retrospective medical record review study using a random sample of incident IBS cases from all Olmsted County, Minnesota providers diagnosed between January 1, 1993 and December 31, 1995. Data was collected on all care and testing provided to the subjects as well as 3-year outcomes related to the IBS diagnosis. RESULTS: Of the 149 IBS patients, 99 were women and the mean age was 47.6 years. No patient had all of the diagnostic tests recommended in the guidelines. 42% had the basic blood tests of CBC and a chemistry panel. Sedimentation rate (2%) and serum thyroxine level (3%) were uncommon. Colon imaging studies were done in 41% including 74% of those over the age of 50. In the 3 years following the diagnosis, only one person had a change in diagnosis and no diagnoses of gastro-intestinal malignancies were made in the cohort. CONCLUSIONS: Primary care practice based diagnostic evaluations for IBS differ significantly from the specialty expert opinion-based guidelines. Implementation of the specialty guidelines in primary care practice would increase utilization with apparent limited improvement in diagnostic outcomes.